THE ROLE OF THE VOCABULARY MAGNITUDE OF THE LANGUAGE IN THE STUDY OF EDUCATIONAL LEXICAL UNITS IN UZBEK AND ENGLISH - Ahmedov, Oybek Saporbayevich; Tilavova , Malika (Журнал иностранных языков и лингвистики, 2023)
The lexicon of the language includes all the words in the language. All the words in the language make up its vocabulary. If the vocabulary of the language is rich, it is easy and fast to express the thought. It is lexicography that opens the door to incomparable knowledge about vocabulary and its structure, types of vocabulary. The vocabulary of the language plays a very important role in the study of educational lexical units in English and Uzbek. And the field that studies dictionaries is lexicography. Before studying educational lexical units in English and Uzbek, in-depth study of this field is required.